2009
DOI: 10.3109/15376510903334862
|View full text |Cite
|
Sign up to set email alerts
|

Determination of alloxan by fluorometric high-performance liquid chromatography

Abstract: A fluorometric, reversed-phase high-performance liquid chromatography (RP-HPLC) method that allows quantitation of low levels of alloxan has been described. The method involved derivatization of alloxan with 500-200,000-fold excess of 1, 2-phenylenediamine (PD) in 0.1 M acetate buffer, pH 4.5 for 15 min at room temperature. The fluorescent product alloxazine (excitation: 382 nm; emission: 435 nm) was then analyzed by RP-HPLC using an Eclipse XDB-C18 (4.6 x 150 mm) column and a mobile phase consisting of 0.1% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…For these compounds, the fragmentation is difficult due to unstable transitions, so the ionization efficiency in ESI is low (Santa, 2011). The pre-column derivatization with ophenylenediamine, which produces Alloxazine, has provided a better way to detect the analyte in question, due to a greater stability (Raghavamenon et al, 2009). Alloxazine is the result of reaction between a primary amine and carbonyl groups with formation of a product containing carbon nitrogen double bonds (Fig.…”
Section: Chromatography and Derivatization Studiesmentioning
confidence: 99%
“…For these compounds, the fragmentation is difficult due to unstable transitions, so the ionization efficiency in ESI is low (Santa, 2011). The pre-column derivatization with ophenylenediamine, which produces Alloxazine, has provided a better way to detect the analyte in question, due to a greater stability (Raghavamenon et al, 2009). Alloxazine is the result of reaction between a primary amine and carbonyl groups with formation of a product containing carbon nitrogen double bonds (Fig.…”
Section: Chromatography and Derivatization Studiesmentioning
confidence: 99%
“…reported the determination of alloxan by the flow injection method, while Raghavamenon et al. reported the fluorometric reversed-phase high-performance liquid chromatography (HPLC) method to detect alloxan at low levels . Electrochemical detection of alloxan was carried out on a modified electrode surface by Paramasivam et al and Monnappa et al …”
Section: Introductionmentioning
confidence: 99%
“…Shpigun et al reported the determination of alloxan by the flow injection method, 9 while Raghavamenon et al reported the fluorometric reversed-phase high-performance liquid chromatography (HPLC) method to detect alloxan at low levels. 10 Electrochemical detection of alloxan was carried out on a modified electrode surface by Paramasivam et al 11 and Monnappa et al 12 Like any other method, the rarely used electrochemical techniques for the quantification of alloxan also deal with the detection of less stable alloxan, resulting in poor accuracy. To The electrochemical methods are developed using glassy carbon electrodes (GCEs) without further modification, making it simple, which could later be extended to screenprinted electrodes in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Research enthusiasts have given ample consideration for developing methods to quantitatively determine bioactive substances such as AL in food products. Goyal et al 11 used HPLC, Raghavamenon et al 12 used fluorometric high performance liquid chromatography, Zheng 13 developed spectrophotometric method while Shpigun et al 14 used flow injection method and Murthy et al 15 used electrochemical techniques. Electrochemical techniques prove to be the most optimistic approach because of its ability to determine analyte levels up to the picomolar range and its automation at nominal cost in comparison with other instruments.…”
Section: Introductionmentioning
confidence: 99%